Breakup the coming end of Canada and the stakes for America - Lamont, Lansing (Norton, 1994)
"Riots in the streets of Montreal. A plunge in the value of Canadian bonds and the Canadian dollar. A terrorist bombing by Cree Indians of a massive Quebec hydroelectric power project. A confrontation between an American oil tanker and a French-supplied Quebec gunboat in the St. Lawrence Seaway. The inexorable pull of the United States, drawing in British Columbia and the Maritime Provinces." "Impossible events? Not so, says Lansing Lamont in this convincing depiction of why and how peaceful and decent Canada is likely to break up over the next ten years. As French-speaking Quebec considers independence, the author warns that such a move would be only the first stage in a painful and tragic unraveling of Canada. In vivid and plausible future scenarios, he shows that the political and economic implications are enormous, not just for Canadians but for Americans, who have long taken their northern neighbor - their largest trading partner and strategic shield - for granted." "The author, a former chief Canada correspondent for Time magazine, has known the country intimately for over twenty-five years, and spent a year of intensive travel and research in writing this book. In his timely and eminently readable narrative, he describes the "anger beneath the smiling land" that is driving Canadians apart. When, in October 1992, the country failed to pass a second constitutional referendum, Canada, he says, lost its "last chance to save itself." The French-speaking Quebecois have obtained the economic confidence as well as the cultural conviction to achieve separation, and English-speaking Canada seems unwilling or unable to stop them. The sad result: the dissolution of the country the United Nations ranked number one in 1992 in terms of economic prosperity and quality of life."